2005
DOI: 10.1523/jneurosci.4335-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Fetal Basis of Amyloidogenesis: Exposure to Lead and Latent Overexpression of Amyloid Precursor Protein and β-Amyloid in the Aging Brain

Abstract: The fetal basis of adult disease (FeBAD) hypothesis states that many adult diseases have a fetal origin. According to FeBAD, injury or environmental influences occurring at critical periods of organ development could result in "programmatic" changes via alterations in gene expression or gene imprinting that may result in functional deficits that become apparent later in life. Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is characterized by excessive deposits of aggregated ␤-amyloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
242
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(261 citation statements)
references
References 36 publications
15
242
0
4
Order By: Relevance
“…In the APP processing pathway, the relative expression of APP coupled with the expression and activity of the APP secretases will likely dictate the amount of Aβ generated. Similar to previous studies [1,24,26], we observe increased APP protein expression in early post-natal animals relative to adult animals. It has been suggested that increased APP levels in young animals is due to its potential role in the developing brain [18].…”
Section: Discussionsupporting
confidence: 91%
“…In the APP processing pathway, the relative expression of APP coupled with the expression and activity of the APP secretases will likely dictate the amount of Aβ generated. Similar to previous studies [1,24,26], we observe increased APP protein expression in early post-natal animals relative to adult animals. It has been suggested that increased APP levels in young animals is due to its potential role in the developing brain [18].…”
Section: Discussionsupporting
confidence: 91%
“…Brain extracts used in this assay were subsamples of those tested in the APP assay. ELISA was performed to quantitatively assay levels of A␤ 40 in different brain extract samples using an Immuno-Biological Laboratories kit that detects human as well as rodent A␤ (27713; Immuno-Biological Laboratories Company, Gunma, Japan), as described previously Basha et al, 2005). The number of samples tested were control and all drug treatments, n ϭ 9, except for 75 mg posiphen, wherein n ϭ 8.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, alterations in this pathway have been widely shown to be related to congenital malformations [27]. Studies on prenatal manipulation of this pathway and its consequences for the offspring have analyzed behavioral, biometric, biochemical or gene expression parameters [28][29][30][31]. In our study, we aimed to assess the impact of hHcy on male offspring by methionine supplementation during pregnancy/ lactation in mice.…”
Section: Discussionmentioning
confidence: 99%